Courtesy stigma of parents of children with Down syndrome: Adaptation process and transcendent stage. Issue 3 (24th December 2021) - Watanabe, Motoko; Kibe, Chieko; Sugawara, Masumi; Miyake, Hidehiko
Abstract: Courtesy stigma, which arises from close connections to people with stigmatized characteristics, negatively affects interpersonal relations. This study aimed to evaluate courtesy stigma and the adaptation process of parents of children with Down syndrome based on semi‐structured interviews with 23 Japanese parents. The interview themes were (a) negatively perceived interpersonal experiences and coping strategies; (b) information disclosure and others' responses; and (c) positively perceived interpersonal experiences. The interview data were transcribed and analyzed based on a grounded theory approach. The results suggested that parents perceived and experienced multidimensional courtesy stigma, and they used various coping strategies categorized in combinations of passive–active and internal–external. All parents disclosed information about their child's diagnosis to others, and reverse disclosure (i.e., revealing own relations with people with disabilities) was characteristically observed thereafter. Through active interaction and reflection, the parents cultivated social relationships, compassion, world views, and community involvement, which led to the transcendent stage. However, internal conflict as a mediator between people with and without Down syndrome re‐emerged even after achieving the transcendent stage. These findings could help to develop interventions in genetic counseling for parents to deal with interpersonal relationship difficulties.